Kidney dosimetry in 777 patients during (177)Lu-DOTATATE therapy: aspects on extrapolations and measurement time points - Sandström, Mattias (EJNMMI Phys, 2020)
PURPOSE: Fractionated peptide receptor radionuclide therapy (PRRT) with (177)Lu-DOTATATE is increasingly applied as an effective treatment for patients with disseminated neuroendocrine tumors. In parallel to dose planning before external beam radiation therapy, dosimetry is also needed to optimize PRRT to the individual patient. Accordingly, absorbed doses to organs at risk need to be calculated during PRRT, based on serial measurements of radioactivity distribution utilizing SPECT/CT. The dosimetry should be based on as few measurements as possible, while still retaining reliable results. The main aim of the present work was to calculate the fractional contribution of the extrapolations of the curve fits for the absorbed dose calculations to the kidneys. The secondary aim was to study agreement between absorbed dose (AD) and the effective half-life (t(eff)) for the kidneys, estimated by means of measurements at one or two time points, in comparison to our current method employing three time points. METHODS: In 777 patients with disseminated neuroendocrine tumors undergoing PRRT, SPECT/CT over the abdomen was acquired at 1, 4, and 7 days after (177)Lu-DOTATATE infusion. The absorbed dose to the kidneys was calculated from SPECT/CT radioactivity distribution data, and the t(eff) and fractional contributions of the extrapolations were estimated, utilizing data from one, two, and three time points, respectively. RESULTS: The fractional contributions from extrapolations before day 1 measurement and after day 7 measurement were approximately 26% and 11%, respectively. The mean differences in absorbed dose, based on one, two, and three time points were small, but with high method dependence for individual patients. The differences in estimated t(eff) were small when it was based on measurements at days 1 and 7, but high for days 1 and 4 time points. CONCLUSION: When assessing simplifications of methods for calculation of the absorbed dose to the kidneys, it was of the uttermost importance to incorporate the fractional contribution for the extrapolations included in the reference method. Measurements at an early and a late time point were found most important. An intermediate measurement contributes with an idea of the goodness of the fit.